Situation of Personal Hygiene Practices Among Senior Citizens - Bohara, Pradeep Kumar (ILAM इलम, 2024)
Ageing is defined by biologists as a continuous process that starts from conception to death. This study focused on elderly individuals aged 60 years and above. It employed a descriptive design and a census method was applied for data through interviews and questionnaires. The primary data was analyzed using a survey research design, descriptive, and exploratory methods. The sample population included 230 senior citizens selected through census sampling techniques. The study revealed that the majority (29.13%) of senior citizens were in the age group of 60-64 years, while the lowest (10.87%) were in the age group of 80 years and above. About 53.48% of the respondents were married, with 31.74% being widows/widowers and 12.61% separated. The majority of the respondents identified as Chhetri and followed the Hindu religion. Additionally, 50.87% were illiterate, while 49.13% were literate. The findings indicated that the status of senior citizens is influenced by factors such as education, economic status, and family support. Most of the elders know about personal hygiene but in practice they are weak.